2007
DOI: 10.1093/annonc/mdm193
|View full text |Cite
|
Sign up to set email alerts
|

Questioning specialists’ attitudes to breast cancer follow-up in primary care

Abstract: Specialists favour a risk adjusted discharge strategy and increased oncology infrastructure in primary care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
73
0
4

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(79 citation statements)
references
References 21 publications
2
73
0
4
Order By: Relevance
“…This is in accordance with previous studies suggesting that specialists have difficulty discharging patients to primary care. 3,9 We also found that only 31% of the GPs used the current breast cancer guideline from the Dutch College of General Practitioners during the follow-up of their patient. Previous studies have shown that clinical guidelines in general practice with low compliance rates were those requiring new knowledge and skills, not easy to follow, not compatible with existing norms and values Table 3 Personal and practice characteristics associated with general practitioners' (GPs') willingness to accept exclusive responsibility for routine breast cancer follow-up at an earlier stage.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…This is in accordance with previous studies suggesting that specialists have difficulty discharging patients to primary care. 3,9 We also found that only 31% of the GPs used the current breast cancer guideline from the Dutch College of General Practitioners during the follow-up of their patient. Previous studies have shown that clinical guidelines in general practice with low compliance rates were those requiring new knowledge and skills, not easy to follow, not compatible with existing norms and values Table 3 Personal and practice characteristics associated with general practitioners' (GPs') willingness to accept exclusive responsibility for routine breast cancer follow-up at an earlier stage.…”
Section: Discussionmentioning
confidence: 83%
“…1,2 Several guidelines exist for follow-up. [3][4][5] In the Netherlands, the current breast cancer guidelines recommend hospital follow-up for 5 years, including yearly mammography. After these 5 years, patients aged >60 years, and treated with breast-conserving therapy, are discharged to their general practitioner (GP) for yearly physical examination and two-yearly mammography.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is reluctance on the part of hospital clinicians to implement these guidelines (Donnelly et al, 2007). Although breast surgeons and oncologists recognise the benefit of reduced clinic workload which comes with discharging patients to general practice, anxiety over perceived lack of GP training and experience in oncology and potential loss of patient outcome data leave them reluctant to follow NICE guidance (Donnelly et al, 2007).…”
mentioning
confidence: 99%
“…Although many specialists favour transferring care of ebc patients, on a risk-adjusted basis, to a primary care physician 3 , and although primary care physicians are willing to play a greater role in follow-up care 4,31 , consideration of the patient perspective is also important 7 . Recently, we conducted 3 online surveys in Canada to determine the views of oncologists, primary care physicians, and patients on the well follow-up care of patients with ebc.…”
Section: Attitudes Of Primary Care Physicians Oncologists and Patiementioning
confidence: 99%